1997
DOI: 10.1111/j.1600-051x.1997.tb01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Subpedicle connective tissue graft versus free gingival graft in the coverage of exposed root surfaces A 5‐year clinical study

Abstract: The authors compared the clinical results obtained in gingival recession correction treatment using free gingival and bilaminar connective subpedicle grafts. 35 patients were treated with free gingival grafts (Group A) and 35 with subpedicle grafts (Group B). Class I and II Miller gingival recessions were chosen for treatment by the 2 procedures. The degree of gingival recession (GR), keratinized tissue (KT) and the exposed root surface area (ERSA) were measured preoperatively and again 5 years post-surgery. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
26

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 22 publications
7
106
0
26
Order By: Relevance
“…Among these techniques, CTG has been conventionally and widely performed. Paolantonio et al 17) compared clinical results obtained in gingival recession correction treatment using free gingival grafts and CTG, and concluded that CTG was expected to provide more reliable root coverage than free gingival graft. A study comparing the GTR technique using an absorbable membrane and CTG also suggested that CTG is more likely than the GTR to achieve complete root coverage 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Among these techniques, CTG has been conventionally and widely performed. Paolantonio et al 17) compared clinical results obtained in gingival recession correction treatment using free gingival grafts and CTG, and concluded that CTG was expected to provide more reliable root coverage than free gingival graft. A study comparing the GTR technique using an absorbable membrane and CTG also suggested that CTG is more likely than the GTR to achieve complete root coverage 8) .…”
Section: Discussionmentioning
confidence: 99%
“…13 Ayrıca, kompozit rezinlerin doldurucu partikülleri mekanik özelliklerini etkileyen önemli faktörlerden sayılmaktadır. 15,16 Piyasadaki kompozitlerin rezin matrislerine yerleştiri-len doldurucu partiküllerin büyüklüğü yıllar geçtikçe, geleneksel büyük boyutlu dolduruculardan, nano-hibrit materyallerdeki çok küçük doldurucu boyutlarına doğru değişmiştir.…”
Section: Gereç Ve Yöntemunclassified
“…Bu kompozit materyalin basma dayanıklılığı değerleri ile mikrohibrit rezin kompozit Esthet-X ve üniversal rezin kompozit Z 250'nin değerleri arasındaki farklar istatistiksel açıdan anlamlıydı (p<0,01). 4,[12][13][14] Bu çalışmada, normal metakrilat bazlı geleneksel kompozitlerinkinden çok daha az polimerizasyon büzül-mesine sahip olduğu ileri sürülen rezin kompozit Silorane, diğerlerinden çok farklı monomer matrise sahip bir materyal olarak kullanıldı. 4 Bunun yanı sıra, kullanılan diğer rezin kompozitlerin içeriğinde farklı metakrilat kombinasyonları yer almaktadır.…”
unclassified
“…La literatura muestra por medio de estudios comparativos que las técnicas bilaminares presentan un mayor grado de predecibilidad cuando el objetivo de los clínicos es obtener completo cubrimiento radicular (15,16). El éxito de esta técnica bilaminar está basada en el incremento del suministro sanguíneo del injerto como es planteado por algunos autores, si se compara con el autoinjerto gingival libre.…”
Section: Introductionunclassified